2022
DOI: 10.1158/1078-0432.ccr-22-2185
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and Cellular Immune Responses against SARS-CoV-2 after Third Dose BNT162b2 following Double-Dose Vaccination with BNT162b2 versus ChAdOx1 in Patients with Cancer

Abstract: Purpose: Cancer patients display reduced humoral responses after double-dose COVID-19 vaccination while their cellular response is more comparable to that in healthy individuals. Recent studies demonstrated that a third vaccination dose boosts these immune responses, both in healthy people and cancer patients. Due to the availability of many different COVID-19 vaccines, many people have been boosted with a different vaccine from the one used for double-dose vaccination. Data on such alternative vaccination sch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Many studies by other authors showed that cancer patients had a reduced humoral response after receiving a double dose of the COVID-19 vaccine compared to healthy individuals [37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies by other authors showed that cancer patients had a reduced humoral response after receiving a double dose of the COVID-19 vaccine compared to healthy individuals [37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Serial boosters may continue to strengthen and help maintain the humoral immune response in the vast majority of patients with cancer under active treatment. Still some patients, including those receiving anti-CD20 therapy, CD19-directed chimeric antigen receptor T-cell therapy and ibrutinib, [11] , [19,28] may require alternative protective measures such as recombinant antibodies or high titer intravenous immunoglobulin.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Several studies of the Omicron (B.1.1.529) subvariants reported heightened capacity for immune evasion, [6] and reduced vaccine effectiveness for first-generation monovalent COVID-19 vaccines. [7] Other reports suggest that additional doses of the monovalent mRNA vaccines, [8,9] heterologous boosting, [10,11] and the bivalent mRNA vaccines provide additional immune protection to SARS-CoV-2 B.1.1.529 infection and severe COVID-19 illness. [12] For patients with cancer, evidence suggests that primer vaccinations elicit lower antibody titers compared to healthy individuals, albeit dependent on disease state, co-morbidities, and anticancer treatment status.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations